Hubungan Latar Belakang Budaya Orang Tua Terhadap Pengasuhan Anak Usia Dini - Rida Amalia; Laily Rosidah; Atin Fatimah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this research is to find out if there is a relationship between parenting and parents' cultural background. This study used quantitative methods with correlational analysis data processing. In this study, 30 parents who have children aged 5-6 years in Benda Village, Sukabumi District, West Java, became the research subjects. Data collection methods used survey techniques and documentation. The analysis test used was Person Product Moment correlation between variable X and variable Y. Based on the results obtained, it can be concluded that there is a significant relationship between parents' cultural background and parenting. This is based on the sign value. 0.000 > 0.05 is considered valid and the Pearson Correlation value of 0.757 indicates a strong interdependence between variables. Thus, there is a clear relationship between parents' cultural background and early childhood care.